2022
DOI: 10.3389/fviro.2022.914888
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: MSH3 homology and potential recombination link to SARS-CoV-2 furin cleavage site

Abstract: A commentary on MSH3 Homology and potential recombination link to SARS-CoV-2 furin cleavage site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 9 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…(Ambati et al, 2022) (research with SARS-like viruses) and the patent (Bancel et al, 2017) (cancer research) can be reasonably extended so that whilst neither includes the integration of an FCS into a CoV, they could have converged into one joint set of laboratory experiments enabling its integration nonetheless? • If the likelihood for the implied sequence homologies is as high as argued in (Dubuy and Lachuer, 2022), what does this mean in terms of biorisk potentials, especially regarding deliberate exploitation? • What do these factors combined mean from an existing biorisk management perspective, especially related to crime risks and deliberate attacks?…”
Section: Thank One Of the Reviewers Of An Earlier Version Of This Art...mentioning
confidence: 99%
See 4 more Smart Citations
“…(Ambati et al, 2022) (research with SARS-like viruses) and the patent (Bancel et al, 2017) (cancer research) can be reasonably extended so that whilst neither includes the integration of an FCS into a CoV, they could have converged into one joint set of laboratory experiments enabling its integration nonetheless? • If the likelihood for the implied sequence homologies is as high as argued in (Dubuy and Lachuer, 2022), what does this mean in terms of biorisk potentials, especially regarding deliberate exploitation? • What do these factors combined mean from an existing biorisk management perspective, especially related to crime risks and deliberate attacks?…”
Section: Thank One Of the Reviewers Of An Earlier Version Of This Art...mentioning
confidence: 99%
“…They also gave a very basic framework of how the purportedly patented sequence could have been integrated into a SARS-like virus, but they leave several questions about the rationale of such a research entertainment unanswered. Additionally, it has been suggested that the specific recombination event may happen very rarely, and, furthermore, the calculated coincidence probability has been contested and published as a Commentary (Dubuy and Lachuer, 2022) to Ref. (Ambati et al, 2022).…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations